Demyelination Disorders 2022
DOI: 10.5772/intechopen.91930
|View full text |Cite
|
Sign up to set email alerts
|

Non-Myelinating Schwann Cells in Health and Disease

Abstract: Non-myelinating Schwann cells (NMSCs) are one of the two major phenotypes of Schwann cells. NMSCs are of different types and have various locations. In the peripheral nervous system, NMSC, named Remak Schwann cells (RSC), accommodate multiple small-caliber axons, forming Remak bundles. NMSC, named perisynaptic/terminal Schwann cells, are found at the distal end of motor nerve terminals at the neuromuscular junction (NMJ). Thus, NMSCs proved to serve different functions according to their distribution such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…Similar morphological differences between these mice were also observed in their sural nerve that mostly contain non-myelinated axons (data not shown). Remak bundles normally consist in a single non-myelinating SC that ensheaths several small C-type axon fibers separately (24). In PCSK9 knockouts, most axons within Remak bundles appeared to fasciculate together (Figure 3E), with an abnormal presence of vacuoles within these bundles (Supplementary figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…Similar morphological differences between these mice were also observed in their sural nerve that mostly contain non-myelinated axons (data not shown). Remak bundles normally consist in a single non-myelinating SC that ensheaths several small C-type axon fibers separately (24). In PCSK9 knockouts, most axons within Remak bundles appeared to fasciculate together (Figure 3E), with an abnormal presence of vacuoles within these bundles (Supplementary figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these cells modulate pain sensitivity in peripheral sensory neuropathies. In accord, it has been demonstrated that even in absence of injury, alterations between axon-Remak cells interactions are followed by neuropathic pain [2,8]. Meanwhile, Schwann cells wrap larger axons of sensory and motor neurons [2,9].…”
Section: Schwann Cells and Nerve Injurymentioning
confidence: 96%
“…in diameter shows conducting action potential less than 1 m/s, whereas large-diameter heavily myelinated axons conduct at a rate of approximately 100 m/s [12].…”
Section: The Anatomy Of Peripheral Nervementioning
confidence: 99%
“…Within a peripheral nerve, there are both myelinated and nonmyelinated nerve fibers. Both types of fibers are supported by Schwann cells, representing the most abundant glial cells of the PNS [12]. Schwann cells exist in two different cell types: Remak cells, or non-myelin Schwann cells, and myelin Schwann cells.…”
Section: The Anatomy Of Peripheral Nervementioning
confidence: 99%